2022
DOI: 10.2147/idr.s383285
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Multidrug-Resistant Pathogens Causing Bloodstream Infections in an Intensive Care Unit

Abstract: Introduction Bloodstream infections are the most severe infections that cause the highest mortality rate, especially in patients admitted to the intensive care unit (ICU). In this study, we aimed to analyze the distribution, resistance patterns and prevalence of MDR (multidrug-resistant) pathogens isolated in blood samples collected from patients with severe invasive infections hospitalized in the ICU. Methods A retrospective study of bacterial pathogens was performed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
1
7
1
Order By: Relevance
“…Our research revealed that 7.91% of the tested Klebsiella pneumoniae strains were resistant to colistin, which is lower than a study conducted in Romania (21%), 12 but slightly higher than a study in Iran (6.9%). 40 This poses a significant public health risk, considering the rapid emergence of MDR Gram-negative bacteria and the limited development of new anti-infective agents.…”
Section: Discussioncontrasting
confidence: 80%
See 3 more Smart Citations
“…Our research revealed that 7.91% of the tested Klebsiella pneumoniae strains were resistant to colistin, which is lower than a study conducted in Romania (21%), 12 but slightly higher than a study in Iran (6.9%). 40 This poses a significant public health risk, considering the rapid emergence of MDR Gram-negative bacteria and the limited development of new anti-infective agents.…”
Section: Discussioncontrasting
confidence: 80%
“…Nearly 90% of the isolated CoNS strains were resistant to penicillin, over 80% to erythromycin, 65.73% to clindamycin, and 50.81% to trimethoprim/sulfamethoxazole, which was much higher than a study conducted in Romania (78.93% resistant to penicillin, 72.96% to erythromycin, and 59.12% to clindamycin). 12 Notably, we detected 2 (0.81%) linezolid-resistant CoNS strains, while a study from China reported a linezolid resistance rate of 1.6%. 31 Linezolid-resistant Staphylococcus has become a new challenge for clinical anti-infective therapy.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…Antimicrobial resistance poses a substantial threat to global health and development, with the prevalence of multidrug resistance becoming increasingly common among pathogenic bacteria. Drug-resistant pathogens are a serious concern in both hospital and non-hospital settings, presenting substantial challenges to the healthcare system, encompassing issues related to the identification, management, and control of infections caused by resistant organisms [ 1 , 2 ]. Therefore, the development and application of new antimicrobial drugs are imminent.…”
Section: Introductionmentioning
confidence: 99%